Strategic Investment And Excess Capacity: The Case Of Malaysian Palm Biodiesel Industry (Malaysian Management Journal, 2014)
With the growing demand of palm biodiesel worldwide, the government has recently announced the implementation of palm biodiesel programme effective July 2014. The implementation will boost the palm biodiesel industry and heighten the demand for palm biodiesel in the domestic market as well as in the international market. This paper thus examines the relationship between the use of strategic investment in excess capacity and the industry entry condition, using logit model. This study covered study period from year 2006 to 2013. The results from this study will further help policymakers to develop policy that is parallel with the condition of the industry.